2021
DOI: 10.1101/2021.03.10.434526
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct generation of subjective vividness and confidence during naturalistic memory retrieval in angular gyrus

Abstract: Subjective experience of remembering is a hallmark of episodic memory, which enables us to monitor experiences, identify mistakes, and adjust our decisions accordingly. A fundamental and enduring puzzle is the origin of confidence in memory; for example, does the confidence during episodic retrieval depend upon the subjective sensed vividness, or does confidence and vividness reflect dissociable introspective processes? The angular gyrus (AnG) exhibits a sensitivity to subjective experience of remembering, but… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
2
1
0
Order By: Relevance
“…The observation that stimulation of angular gyrus selectively reduced the link between memory precision and self-referential reality monitoring decisions is consistent with proposals that functioning of angular gyrus may contribute to the self-referential quality of memories (Bonnici et al, 2018;Rugg & King, 2018;Weniger et al, 2009;Yazar et al, 2012Yazar et al, , 2014Yazar et al, , 2017. This selfreferential mnemonic function may involve integrating multiple modalities of retrieved features, such as visual and auditory details (Yazar et al, 2017), within an egocentric, first-person perspective framework (Bonnici et al, 2018), in order to reconstruct rich and subjectively vivid mnemonic representations that are imbued with a sense of self-agency (Simons et al, 2021;Zou & Kwok, 2021).…”
Section: Discussionsupporting
confidence: 83%
“…The observation that stimulation of angular gyrus selectively reduced the link between memory precision and self-referential reality monitoring decisions is consistent with proposals that functioning of angular gyrus may contribute to the self-referential quality of memories (Bonnici et al, 2018;Rugg & King, 2018;Weniger et al, 2009;Yazar et al, 2012Yazar et al, , 2014Yazar et al, , 2017. This selfreferential mnemonic function may involve integrating multiple modalities of retrieved features, such as visual and auditory details (Yazar et al, 2017), within an egocentric, first-person perspective framework (Bonnici et al, 2018), in order to reconstruct rich and subjectively vivid mnemonic representations that are imbued with a sense of self-agency (Simons et al, 2021;Zou & Kwok, 2021).…”
Section: Discussionsupporting
confidence: 83%
“…Turning to the possible neurocognitive basis of memory precision and reality monitoring, stimulation of angular gyrus selectively reduced the observed link between memory precision and self-referential reality monitoring decisions, consistent with proposals that functioning of angular gyrus may contribute to the self-referential quality of memories (Bonnici et al, 2018;Rugg & King, 2018;Weniger et al, 2009;Yazar et al, 2012Yazar et al, , 2014Yazar et al, , 2017. This self-referential mnemonic function may involve integrating multiple modalities of retrieved features, such as visual and auditory details (Yazar et al, 2017), within an egocentric, first-person perspective framework (Bonnici et al, 2018), in order to reconstruct rich and subjectively vivid mnemonic representations that give rise to a sense of self-agency (Simons et al, 2022;Zou & Kwok, 2021).…”
Section: Discussionsupporting
confidence: 81%
“…Another issue that is beyond the scope of the current study is the degree to which the effects reported here depend on the subjective experience of remembering versus the objective experience of stimulus repetition. A compelling body of evidence indicates that the angular gyrus is involved in (Hutchinson et al, 2014; Kuhl & Chun, 2014; Ramanan et al, 2018) and even necessary for (Simons et al, 2010; Tibon et al, 2019; Yazar et al, 2014; Zou & Kwok, 2022) the subjective experience of remembering. In contrast, memory effects in OTC may be more closely related to objective effects of stimulus repetition (Sayres & Grill-Spector, 2006; Ward et al, 2013).…”
Section: Discussionmentioning
confidence: 99%